“Islam Agama Semua Nabi” Dalam Perspektif Al-Qur’an - Moh. Ali Wasik (UIN Sunan Kalijaga Yogyakarta, 2016)
This article examines the religions held by the messengers of Allah, as it represented in the Qur’an. It explains that the religion brought by the messengers of Allah is Islam. Islam, in the sense of the non-Muhammadan religion, can be seen as the attribute or the adjective entity, whereas Islam in the religious sense which brought by the prophet Muhammad, refers to both the attribute and the name. The distinguishing character between between pre-“Islamic” Muhammad and Islam brought by the last prophet lies in the difference of the “syari’ah”. However, the goal remains the same; to perform the commands of one God, which is the “tauhid”. Therefore, the Qur’an doesn’t conform the notion that the apostles were Jewish or Christian, but they are the messengers of God who brought “Islam”.[Artikel ini mengkaji agama-agama yang dianut oleh utusan Allah swt. sebagaimana dalam al-Qur’an. Dalam artikel ini dijelaskan bahwa semua Agama yang dibawa oleh para Rasul utusan Allah swt adalah Islam. Islam dalam pengertian agama para Rasul selain nabi Muhammad bermakna sifat, sedangkan Islam dalam pengertian agama yang dibawa nabi Muhammad bermakna sifat dan sekaligus nama. Adapun yang membedakan antara agama para Rasul sebelum nabi Muhammad adalah syari’ah-nya, namun demikian tujuannya tetap satu, yaitu menjalankan syari’ah dari satu Tuhan, yang kemudian bermakna tauhid. Tidak dibenarkan oleh al-Qur’an apabila ada anggapan bahwa para Rasul beragama Yahudi maupun Nasrani, mereka adalah para utusan Allah yang membawa Agama Islam.]